Experimental And SPH Study Of Cold Spray Impact Between Similar And Dissimilar Metals - Abd. Manap, Abreeza Noorlina; Omar, Nooririnah; Misran, Mohamad Harris; Okabe, T; Ogawa, K (Surface Engineering, 2014)
-